Legal Remedies and Franchise Protection in Termination of the Franchise Agreement Unilaterally by the Franchisor Before the Termination of the Agreement - Wardana, Arya Salwa; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
The franchise agreement is a written agreement made by both parties between the franchisor and the franchisee which contains the rights and obligations of each party as well as legal consequences that must be obeyed by each party. In implementing a franchise agreement, the possibility of problems or disputes is very open, so it is not uncommon for the franchisor to terminate the agreement unilaterally. This study uses normative legal research methods due to a problem of norms, namely the absence of norms. This study uses 2 approaches, namely the statutory approach and the conceptual approach. Based on the discussion and research results, it is known that basically the franchise agreement cannot be terminated unilaterally either from the franchisor or from the franchisee before the end of the agreement, unless there are void conditions stated in the contents of the agreement and have been agreed upon by the parties. As for legal remedies that can be taken by franchisees who suffer losses due to unilateral termination by the franchisor, namely filing a claim for damages by default.